Sylvia & Aki - Conkling, Winifred (<> Yearling Book, 2013)
At the start of World War II, Japanese-American third-grader Aki and her family are sent to an internment camp in Poston, Arizona, while Mexican-American third-grader Sylvia's family leases their Orange County, California, farm and begins a fight to stop school segregation